Myasthenia gravis and community-acquired pneumonia: therapeutic challenges - Chen, Xueying; Ding, Jianbo; Zhang, Jiali; Dai, Haibin; Yu, Lingyan (Frontiers in Pharmacology, 2025)
Myasthenia gravis (MG) patients are highly susceptible to community-acquired pneumonia (CAP) due to the need for immunosuppressive therapies and aspiration risks, with CAP representing the leading infectious cause of mortality in this population. The intersection of MG and CAP poses unique challenges for the management of anti-infective agents and immunosuppressants. There is currently no systematic literature review addressing these issues, as previous reviews have been limited to one of these aspects. This review synthesizes evidence on the pharmacotherapeutic challenges associated with MG-CAP comorbidity, focusing on three key areas: avoiding antibiotics that exacerbate neuromuscular junction symptoms, minimizing drug interactions, and managing infection-adjusted immunosuppressants. Through a comprehensive synthesis of literature, we provide recommendations for optimizing antibiotic selection and immunosuppressants while tailoring immunosuppressive strategies according to CAP severity grading. This facilitates optimal management of both MG and infection control, highlighting the need for dynamic, patient-centered approaches. This clinical decision-making tool serves as a practical reference for physicians in the absence of established guidelines or expert consensus for managing this complex patient population.